The State-Trait Cheerfulness Inventory State Version–Short Form (STCI-S18): An Examination of Language Use and Psychometric Properties. Issue 4 (4th July 2022) - Lau, Chloe; Chiesi, Francesca; Saklofske, Donald H.; Ruch, Willibald
Abstract: The State-Trait Cheerfulness Inventory–State Version (STCI-S) measures three states of cheerfulness, seriousness, and bad mood as the temperamental basis of humor. The present study investigates (1) the development and psychometric validation of a newly developed short version and (2) test-criterion validity with state measures and language use. Study 1 ( N = 933) confirmed the three-dimensional structure, and both the short and standard versions demonstrated strong psychometric properties. Study 2 ( N = 617) replicated these findings in a separate sample. Study 3 ( N = 750) demonstrated expected intercorrelations with self-report state measures (i.e., inspiration, self-esteem, depression, anxiety). Participants were randomized to expressive writing conditions (i.e., writing about a retrospective cheerful, serious, or bad mood scenario). Unacquainted judges' and participants' ratings of three states in their respective scenarios converged (.44 < r < .62). Retrospective states cheerfulness, seriousness, and bad mood were associated with linguistic categories (e.g., emotional tone, clout, achievement, insight) identified in the Linguistic Inquiry and Word Count (LIWC) software. The impact of personality states on word usage may only be evident in specific contexts and situations. Presence of distinctive language use in these writing samples further demonstrated test-criterion validity and practicality of the STCI-S18.